The construction of placeness in traditional opera from the perspective of structuration theory: A case study of Huangmei Opera in Anqing, China - Fang Zhu; Qin Su; Jiahui Xu; Lei Zhu (PLoS ONE, 2025)
Traditional opera is continuously involved in the construction of placeness because of its close connection with local culture, and the flow of the meaning of placeness has become a hot spot of cultural geography research. This study examines the driving factors and mechanisms of constructing placeness in Huangmei Opera from the perspective of structuration theory. It adopts qualitative research and positivist methodology to analyze the mutual influence and constructive relationship between Huangmei Opera and placeness. The results reveal that under the structural adjustment of the cultural system reform, multiple subjects respond to the impact of the structural adjustment through the action practices of place marketing and leisure participation, combined with the elements of placeness that the city itself possesses. The study confirms that Huangmei Opera, with its local characteristics, is a quintessential example of placeness construction and that Huangmei Opera achieves placeness construction through the interplay of structure, action, and place.